2011
DOI: 10.1002/biof.187
|View full text |Cite
|
Sign up to set email alerts
|

Xanthoangelols isolated from Angelica keiskei inhibit inflammatory‐induced plasminogen activator inhibitor 1 (PAI‐1) production

Abstract: The folk medicine Angelica keiskei (Ashitaba) exhibits antitumor, antioxidant and antidiabetic activities and it has recently attracted attention as a health food. Ashitaba is thought to have antithrombotic properties, but this has not yet been scientifically proven. The elevation of plasma plasminogen activator inhibitor 1 (PAI-1), an inhibitor of fibrinolysis results in a predisposition to the risk of thrombosis. The present study showed that Ashitaba exudates injected intraperitoneally and orally administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…TNF-α, a player in inflammation responses, is also involved in the induction of PAI-1 expression. Again, chalcones in ashitaba, namely compounds 2, 3, 5, and 6, were found to suppress activities induced by TNF-α, resulting in a reversal of PAI-1 increase in human umbilical vein endothelial cells [35]. In another study, 1 and 2 illustrated dose-dependent antiplatelet activity against a number of platelet aggregation inducers, including collagen-, phorbol 12-myristate 13-acetate (PMA), and platelet-activating factor (PAF) in washed rabbit platelets [37].…”
Section: Antithrombotic Activitymentioning
confidence: 94%
See 1 more Smart Citation
“…TNF-α, a player in inflammation responses, is also involved in the induction of PAI-1 expression. Again, chalcones in ashitaba, namely compounds 2, 3, 5, and 6, were found to suppress activities induced by TNF-α, resulting in a reversal of PAI-1 increase in human umbilical vein endothelial cells [35]. In another study, 1 and 2 illustrated dose-dependent antiplatelet activity against a number of platelet aggregation inducers, including collagen-, phorbol 12-myristate 13-acetate (PMA), and platelet-activating factor (PAF) in washed rabbit platelets [37].…”
Section: Antithrombotic Activitymentioning
confidence: 94%
“…Tumor necrosis factor alpha (TNF-α) has been implicated as an important participant in the induction of inflammation [32] and is regulated by transcription factors activator protein 1 (AP-1) and the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB). Ashitaba extract and compound 2 were shown to inhibit inflammation induced by TNF-α in male kwl ICR mice [35]. Another study determined that isolated compounds 1 and 2 had similar TNF-α suppressing effects in RAW264 macrophages [32], and compound 5 induced suppression in porcine aortic endothelial cells [33].…”
Section: Oxidative Stress Relief and Anti-inflammatory Activitymentioning
confidence: 98%
“…We reported that xanthoangelol isolated from Angelica keiskei inhibits PAI-1 increases induced by lipopolysaccharide (LPS) in mouse plasma and by TNF-α in culture media of HUVEC [12]. We also showed that chrysin, a naturally occurring flavone, a type of flavonoid found in plants such as passion flower and chamomile, inhibits the TNF-α induced PAI-1 increase in the culture medium of endothelial cell line [13].…”
Section: Introductionmentioning
confidence: 78%
“…Seven chalcones 1-7 (Fig. 1A) were isolated as active principles from A. keiskei by repeated column chromatography and their purity was analyzed by HPLC (Shimadzu HPLC system with UV monitor at 254 nm; l-Bondapak C 18 column, 10 lm, 10 · 300 mm; 60% aqueous MeOH as eluent; flow rate 2.0 mL/min): 4-hydroxyderrcin (1), xanthoangelol E (2), xanthoangelol D (3), xanthokeismin A (4), xanthoangelol B (5), xanthoangelol (6), and xanthoangelol F (7). The structures of these chalcones 1-7 were identified by 1 H-and 13 C-NMR spectra, which were consistent with the previously reported spectroscopic data.…”
Section: Test Materialsmentioning
confidence: 99%
“…It has been reported that A. keiskei contains various bioactive chalcones and coumarins, showing antioxidant, 2 antidiabetic, 3 chemopreventive, 4,5 and anti-inflammatory activities. 6,7 Lee et al reported that the hexane fraction of A. keiskei inhibited the production of lipopolysaccharide (LPS)-induced nitric oxide (NO) and prostaglandin E 2 (PGE 2 ) through downregulation of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) proteins and mRNA. 8 Another study demonstrated that chalcones isolated from A. keiskei attenuate the production of interleukin-6 (IL-6) in tumor necrosis factor-a (TNF-a)-stimulated osteoblast cells.…”
Section: Introductionmentioning
confidence: 99%